A Simple Correction Term to Model Infiltration in Water‐Repellent Soils. Issue 2 (18th February 2021) - Abou Najm, M. R.; Stewart, Ryan D.; Di Prima, Simone; Lassabatere, Laurent
Abstract: Soil water repellency can substantially alter hydrologic processes, particularly the ability of soils to infiltrate water. Water repellency often changes through time, making it difficult to simulate infiltration behaviors of water‐repellent soils using standard models. Here, we propose a simple rate‐based correction term that starts with a value of zero at the beginning of the infiltration process ( t = 0) and asymptotically approaches 1 as time increases, thus simulating decreasing soil water repellency through time. The correction term can be used with any infiltration model. For this study, we selected a simple two‐term infiltration equation and then, using two data sets of infiltration measurements conducted in soils with varying water repellency, compared model error with versus without the added term. The correction substantially reduced model error, particularly in more repellent soils. At the same time, the rate constant parameter introduced in the new model may be useful to better understand dynamics of soil water repellency and to provide more consistent interpretations of hydraulic properties in water‐repellent soils. Key Points: We propose a simple correction term for infiltration models to characterize water repellency in infiltration models One hundred and sixty five infiltration experiments from three different ecosystems and levels of water repellencies were used to demonstrate model effectiveness The one parameter correction substantially reduced model error and reflected the changing rate of water repellency during infiltration